2012
DOI: 10.1155/2012/634048
|View full text |Cite
|
Sign up to set email alerts
|

Weight and Body Composition Changes during the First Three Years of College

Abstract: Differences in weight, body mass index (BMI), percent and absolute body fat, fat-free mass, and waist circumference were investigated in a group of males and females during the first three years (from 2007 to 2010) of college. Significant three-year gains were observed for weight 2.1 ± 4.7 kg, BMI 0.7 ± 1.6 kg/m2, percent body fat 2.7 ± 3.3%, and fat mass 2.3 ± 3.5 kg. A significant loss of fat-free mass, −0.5 kg, was observed among females. Absolute gains in weight, BMI, and percent and absolute body fat were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
1
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 30 publications
0
47
1
5
Order By: Relevance
“…Similarly, Nicoteri and Miskovsky [21] found that 32% of students were overweight or obese at the end of the senior or graduate year. Although, this does not seem to be a consensus in the literature, because some studies, such as Gropper et al [14] and Racette, Deusinger, Strube, Highstein, and Deusinger [22] found that the percentage of overweight and obese students was lower, at 24% at the end of the junior year and 18% at the end of the sophomore year.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Similarly, Nicoteri and Miskovsky [21] found that 32% of students were overweight or obese at the end of the senior or graduate year. Although, this does not seem to be a consensus in the literature, because some studies, such as Gropper et al [14] and Racette, Deusinger, Strube, Highstein, and Deusinger [22] found that the percentage of overweight and obese students was lower, at 24% at the end of the junior year and 18% at the end of the sophomore year.…”
Section: Discussionmentioning
confidence: 94%
“…The literature shows that among university students, weight gain is associated with poor eating habits, stress, and lower physical activity following the transition from a structured high school environment to university [12,13,14]. Because students do experience important weight changes, universities need to focus on increasing health promotion to help them maintain/adopt healthy behaviors [13].…”
Section: Introductionmentioning
confidence: 99%
“…Transition into a romantic relationship or marriage can cause behavioral changes that lead to the development of obesity (The and Gordon-Larsen 2009;Gordon-Larsen et al 2004), but there is nothing biologically critical about the exact age when this occurs, for example. The same might be true for starting university (Gropper et al 2012), leaving the army (Littman et al 2013), and retiring (Morris et al 1992). The timing of rapid change in a known biological structure/function is critical for the experience of specific environmental stimuli to cause permanent alterations and predict long-term outcomes (Cameron and Demerath 2002).…”
Section: Critical Periods and Transitionsmentioning
confidence: 93%
“…Desouky et al (2014) evoked the presence of non-communicable diseases risk factors of among female university students. Gropper et al (2012) demonstrated that poor eating habits and limited physical activity, in adolescence, could be the cause of serious health problems (osteoporosis, obesity, hyperlipedemia, cardiovascular disease, type 2 diabetes, arthritis, impaired mobility, and cancer), later in life.…”
Section: Discussionmentioning
confidence: 99%